Management of difficult urticaria - Yadav Sudha; Bajaj A (Wolters Kluwer Medknow Publications, 2009)
Chronic urticaria, a major health problem causing patient′s distress, induces often physicians′ dilemma while dealing with its etiology, investigations and management. Clinical approach of such cases should include apart from clinical history and physical examination laboratory investigations like routine blood test, thyroid profile, etc. as well as sometimes special test like autologous serum skin test. Management includes reassurance, avoidance of precipitating factors, treatment of underlying disorders, and non-pharmacological approach along with pharmacotherapy. First line drug therapy comprises non-sedative and sedative antihistamines, second line doxepin, nifedipine, leukotriene-inhibitors, sulfasalazine, etc. and third line cyclosporine, dapsone, colchicin, etc.